Instituições públicas de ensino superior do Amapá no contexto da pandemia da Covid-19: iniciativas e parcerias por meio da governança colaborativa - Pinheiro Júnior, Luiz Augusto dos Santos (2023)
At the beginning of 2020, Covid-19 became known in Brazil, given the scenario caused, mutual assistance between social actors and the State was necessary so that a slowdown in contagion could be achieved. It was in this context that Public Institutions of Higher Education (HEI) revealed its importance, with the help of federative entities, and a model of collaboration was strengthened, which the doctrine agreed to call “Collaborative Governance”. A type of collaboration that has its own characteristics, and in the State of Amapá its strengthening was evident, based on statements in public documents and made available by those involved in collaborative actions. Thus, this research aimed to analyze the theoretical constructs for the configuration of a conditional collaborative governance by Kellas (2010), and Ansell and Gash (2007) in the collaborations carried out in the context of the covid-19 pandemic, between the government and institutions public higher education institutions in the State of Amapá. The theoretical foundation discusses the historical origins of Collaborative Governance, and its definition, as well as the models and theoretical constructs of collaborative governance. This is an applied study, descriptive and with a qualitative approach. As for the technical data collection procedures, it is characterized as field, bibliographic and documentary research, using secondary documents originating from stakeholder portals (interested parties), with the purpose of identifying possible collaborations established between public higher education institutions and interested parties in the context of the pandemic, as well as interviews with participants in the collaborative process through the application of a questionnaire with discursive questions. This research sought to identify, based on the theoretical constructs established by Ansell and Gash (2008) and the constructs established by Kellas (2010), the configuration of collaborative governance between Public Heis in the State of Amapá and interested parties such as federative entities and actors social institutions, as well as third sector entities and society in the State, as well as verifying the results obtained and difficulties encountered in the implementation of collaborative actions. With the result, it was verified that of the three actions analyzed (Qualifica Mais Progredir – Ifap, Availability of Beds at the University Hospital to the Government of Amapá-Unifap and Amapá Jovem Universitário – Ueap) only the Qualifica Mais Progredir program met the theoretical construct for configuration of Collaborative Governance, knowledge was produced that contributed to the increase and improvement of the ways in which Public Higher Education Institutions in Amapá operate, as well as the improvement of Collaborative Governance in the State.